52.1k views
5 votes
Differentiate. y = (x2 - 2x + 6) et O (2x - 2) ex (x2 + 4x + 4) ex O (x2 + 4) ex + 4x + 6​

Differentiate. y = (x2 - 2x + 6) et O (2x - 2) ex (x2 + 4x + 4) ex O (x2 + 4) ex + 4x-example-1

1 Answer

5 votes

Answer:

y' = (x² + 4)eˣ

Explanation:

Power rule: y' = f'(x)g(x) + f(x)g'(x)


(d)/(dx) [e^x]=e^x

Step 1: Write equation

y = (x² - 2x + 6)eˣ

Step 2: Differentiate

  1. Power rule: y' = eˣ(2x - 2) + eˣ(x² - 2x + 6)
  2. Factor out eˣ: y' = eˣ[2x - 2 + x² - 2x + 6]
  3. Combine like terms: y' = eˣ(x² + 4)
  4. Rewrite: y' = (x² + 4)eˣ
User Uday Sravan K
by
5.0k points